Pemurnian Biogas dengan Metode Adsorbsi pada Variasi Waktu Pemurnian dan Laju Aliran menggunakan Adsorben Arang Aktif dan Silika Gel - Abdul Mukhlis Ritonga; Masruhi Masruhi; Dewi Novita (Journal of Agricultural and Biosystem Engineering Research, 2021)
Biogas purification is an effort to increase the calorific value of biogas. The CO2 content in biogas causes the calorific value of the biogas to decrease, so it is necessary purification is carried out to reduce CO2 gas levels and to increase gas levels CH4. The research objectives were 1)To determine the effect of refining time on quality biogas, 2)Knowing the effect of gas flow rate on purification on the quality of the biogas produced, and 3) Determine the duration of purification and the best gas flow rate for purification biogas. The research method used a completely randomized design (CRD) with two factors namely the purification time (15, 20, and 25 minutes) and the gas flow rate (2,4, and 6 L/min) respectively repeated three times, then analyzed the data using the ANOVA test and followed by the DMRT test. The results showed a C/N ratio of 19.46%, the average substrate temperature was 30.23°C, the average pH was 7.3, the total solid was 7.217, and volatile solid of 79.459. ANOVA test results show that there is a significant effect on methane content, while carbon dioxide content has no effect real. The best purification time and biogas flow rate were 25 minutes (178,018.01 ppm) and 6 L/minute (474,744.3 ppm) because it produces the highest methane content, while for the content carbon dioxide at a purification time of 20 minutes (1201.62 ppm) and a gas flow rate of 4 L/minute (52,012.4 ppm) due to produces the lowest levels of carbon dioxide